Direct imaging of structural disordering and heterogeneous dynamics of fullerene molecular liquid - Jeongheon Choe (Nature Portfolio, 2019)
Understanding the structural changes in disordered non-equilibrium materials is important for their processing, yet it remains experimentally challenging to follow the dynamics. Here, Choe et al. image the first-order like transition from crystal to liquid in a model molecular system adsorbed on graphene by tracking individual molecules in real time.